2003
DOI: 10.1111/j.1365-2621.2003.tb14171.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pyrazine and Flavor Variations in Peanut Genotypes During Roasting

Abstract: During peanut roasting, pyrazine compounds correlate highly with roasted flavor and aroma. Although roast color measurement is used to predict roasted flavor in peanuts, there are known variations between roast color and flavor development among genotypes. A method for measuring pyrazines using headspace solid-phase microextraction (SPME) was developed and 4 peanut genotypes were roasted and analyzed under a variety of time-temperature combinations. Peanut genotypes differed in roasted flavor and aroma, regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 18 publications
11
102
2
Order By: Relevance
“…1-methyl-1H-pyrrol (associated with sweet and woody odour) and 2,5-dimethylpyrazine (associated with sweet, malty odours) are two of the most reported aromatic components in roasted peanuts (Braddock, Sims, & O'Keffe, 1995;Ho et al, 1981;Ng, Dunford, & Chenault, 2008; and were also among the compounds detected at the highest concentrations in this study. In fact, some past researchers went further to suggest that 2,5-dimethylpyrazine is the compound with the single highest correlation with roasted peanut aroma, followed by 2,3,5-trimethylpyrazine and 2,3-dimethylpyrazine (Baker et al, 2003), which were also detected in this research, even though the flavour activity of 2,5-dimethylpyrazine has been since disproven ). 2-methylpyrazine, 2,6-dimethylpyrazine, 2,3,5-trimethylpyrazine, and ethylpyrazine often cited in peanut shelf life studies (Mei, Qi, Chang-sheng, Chang, & Feng-hong, 2011;Reed et al, 2002; can also be found in the same table.…”
Section: Resultssupporting
confidence: 49%
See 4 more Smart Citations
“…1-methyl-1H-pyrrol (associated with sweet and woody odour) and 2,5-dimethylpyrazine (associated with sweet, malty odours) are two of the most reported aromatic components in roasted peanuts (Braddock, Sims, & O'Keffe, 1995;Ho et al, 1981;Ng, Dunford, & Chenault, 2008; and were also among the compounds detected at the highest concentrations in this study. In fact, some past researchers went further to suggest that 2,5-dimethylpyrazine is the compound with the single highest correlation with roasted peanut aroma, followed by 2,3,5-trimethylpyrazine and 2,3-dimethylpyrazine (Baker et al, 2003), which were also detected in this research, even though the flavour activity of 2,5-dimethylpyrazine has been since disproven ). 2-methylpyrazine, 2,6-dimethylpyrazine, 2,3,5-trimethylpyrazine, and ethylpyrazine often cited in peanut shelf life studies (Mei, Qi, Chang-sheng, Chang, & Feng-hong, 2011;Reed et al, 2002; can also be found in the same table.…”
Section: Resultssupporting
confidence: 49%
“…Four sensory attributes, namely roasted peanut, sweet, dark roast and raw bean aromas were modelled with .70 respectively. The roasted peanut attribute had a poor R 2 coefficient, and the model should not be considered well-fitting, but the observations are nonetheless included here, as they are in good agreement with the literature (Baker et al, 2003;Braddock et al, 1995;Ho et al, 1981;Ho C.T. et al, 1983;Xiao et al, 2014).…”
Section: Correlations Between Flavour Attributes and Volatile Headspasupporting
confidence: 63%
See 3 more Smart Citations